Effects of Alternative Work Schedule Preferences on Job Performance, Satisfaction and Morale: Evidence from Community Colleges - Wright, Brent C (My University, 2026)
Amid the government-mandated shutdowns and work-from-home orders due to the COVID-19 pandemic, businesses have been forced to scramble to find ways to immediately cut costs and sustain productivity while being denied access to their facilities. Many industries, including education, were forced into alternative work schedules (AWS; telecommuting and compressed time) to prevent in-person contact and the potential spreading of the virus. Other businesses and organizations were forced into AWS to immediately cut operation costs to save the business. However, there is little research on the benefits and drawbacks of the shift to AWS. This study aimed to fill that gap in understanding the effects of an unanticipated forced shift to specific AWS: teleworking and flextime within the community college setting as employees bring with them their unique perceptions of and preferences for AWS. The population comprised employees and supervisors at three State of Alabama community colleges. The basic research design for the study was a cross-sectional survey of employees and supervisors about their experience with the benefits and drawbacks of alternative work schedules. Multiple linear regression and factor analysis were used for the data analysis. This research specifically examined the effect of a forced shift to AWS and employees’ preferences for AWS on employee job satisfaction, performance, and morale. Using data collected from employee surveys, each variable (job, satisfaction, performance, and morale) was measured individually and collectively to determine the impact on each resulting from the AWS shift. The results of this research will be beneficial to any community college system and may help to provide leaders of other organizations, government agencies, private businesses, or educational institutions with knowledge and insights into potential outcomes for their own institutions if they realize a need to use AWS to immediately cut cost or are faced with another government-mandated shutdown.
Keywords: Management; Economics; Dissertations, Academic; Community colleges--Administration; COVID-19 Pandemic (2020-2023); Hours of labor